(untitled) (The Batuk, 2021)
This descriptive study aims at exploring the challenges and opportunities of e-banking in the Nepalese banking sector. The required data are collected from bank employees by applying a self administered questionnaire, semi-structured interviews and the desktop research. The findings demonstrate that banks expand to e-banking services in order to remain competitive, to update themselves with new technological developments and to minimize transaction cost and to facilitate customers. The major challenges faced the e-banking customers are non-familiarity with advanced technology, internet connection problems, problems regarding security and privacy. These challenges have a negative influence on the adoption of e-banking services by customers in Nepal. To overcome the challenges, Nepalese banking industry should invest on adopting the most secured and trustworthy e-banking system and educating customers on the use and importance of e-banking regularly.